2009
DOI: 10.2174/138920309789351930
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregating Chaperones: An Unfolding Story

Abstract: Stress, molecular crowding and mutations may jeopardize the native folding of proteins. Misfolded and aggregated proteins not only loose their biological activity, but may also disturb protein homeostasis, damage membranes and induce apoptosis. Here, we review the role of molecular chaperones as a network of cellular defenses against the formation of cytotoxic protein aggregates. Chaperones favour the native folding of proteins either as "holdases", sequestering hydrophobic regions in misfolding polypeptides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
77
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 147 publications
1
77
0
Order By: Relevance
“…Although all of the processes described above provide plausible mechanisms for how c-Abl activity might support TfR1 recycling back to the cell surface, we focused our attention on the action of the cytoplasmic chaperone Hsc70, well known to mediate a diverse set of cellular functions that include the uncoating of clathrin vesicles (44 -46), facilitating appropriate protein folding (47), and directing cellular organelles into the autophagic pathway (48,49), to name just a few. The interactions between this chaperone and the TfR1 upon inhibition of c-Abl by imatinib as assessed by co-IP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although all of the processes described above provide plausible mechanisms for how c-Abl activity might support TfR1 recycling back to the cell surface, we focused our attention on the action of the cytoplasmic chaperone Hsc70, well known to mediate a diverse set of cellular functions that include the uncoating of clathrin vesicles (44 -46), facilitating appropriate protein folding (47), and directing cellular organelles into the autophagic pathway (48,49), to name just a few. The interactions between this chaperone and the TfR1 upon inhibition of c-Abl by imatinib as assessed by co-IP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, several proteins have been identified that, like IscS, preferentially bind and stabilize a disordered target protein (20)(21)(22). Many of these are chaperone proteins that rescue misfolded proteins (23)(24)(25) or are proteins involved in protein degradation (26)(27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, DnaK can perform this function when assisted by its two cochaperones, a J-domain-containing protein (either DnaJ, CbpA, or DjlA; Genevaux et al 2007) and the nucleotide exchange factor GrpE (Sharma et al 2009). Specificity of the chaperone system is conferred primarily by the DnaJ co-chaperone, which recognizes and binds to a misfolded polypeptide (Hinault et al 2010), followed by the binding of the polypeptide to a "low-affinity" DnaK, which becomes entrapped upon hydrolyzing ATP.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The strong cyto-protective, even curing effects of the Hsp70-Hsp40 chaperones systems, both in the cytoplasm and in mitochondria can be attributed to their ability to act as polypeptide unfolding enzymes that can target cytotoxic misfolded and aggregated protein conformers (Sharma et al 2009;Sharma et al 2010). In organisms and cellular compartments that also express Hsp100/ClpB homologues, the Hsp70-Hsp40 unfoldase chaperone systems benefit from a powerful synergic mechanism of forceful disaggregation that may act both upstream and downstream to the polypeptide unfoldase activity of Hsp70 chaperones (Glover and Lindquist 1998;Goloubinoff et al 1999;Weibezahn et al 2005).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%